Notorious C.H.O. - Cho, Margaret; Machado, Lorene; Cho Taussig Productions; Wellspring Media (New York Wellspring Media, 2002)
A stand-up comedy performance by comedian Margaret Cho.
Hello margaret -- Gag reflex -- Scotland -- Colon irrigation -- Heavy flow -- Limited dreams -- Mommy and daddy -- Personal ads -- Hershey's kiss -- Be kind, rewind -- Close -- The G spot -- One of the muppets -- Sex club -- Get ugly -- Food issues -- Being single -- Long overdue -- Mommy in Israel -- Notorious.
Special features: theatrical trailer; Margaret Cho filmography; deleted scenes; animated short film ("Grocery store"); "Notorious" movie shoot; making-of featurette; optional audio commentary (by Mrs. Cho and friends).
Director of photography, Kirk Miller ; music, Greg Burns [and others].
Starring Margaret Cho.
Filmed on location at Louise M. Davies Symphony Hall in San Francisco, September 29, 2001 and the Paramount Theatre in Seattle, November 11, 2001.
DVD; Dolby digital 5.1 surround or Dolby digital stereo.
112806
Keywords: Cho, Margaret -- Humor; 2000-2099; Asian American wit and humor; Women -- Sexual behavior -- Humor; Body image in women -- Humor; Women -- Identity -- Humor; Bisexual women -- Humor; Asian American comedians; American wit and humor -- 21st century; San Francisco (Calif.) -- Humor; California -- San Francisco; Comedy films; Stand-up comedy routines; Humor; Feature films